Teaching Health as a Human Right in the Undergraduate Context: Challenges and Opportunities - Salhi, Bisan A. (Health Hum Rights, 2019)
This paper explores the possibility of a pedagogy about health and human rights that is understandable and persuasive to undergraduate students yet does not succumb to a reductive dualism of optimism and pessimism. In 2014, we presented the topic of health and human rights in an introductory undergraduate global health course in conjunction with the exhibit “Health is a Human Right: Race and Place in America” at the Centers for Disease Control in Atlanta, Georgia. The exhibition highlighted the United States’ complicated legacy and failures of health and human rights, with an emphasis on ongoing racial and socioeconomic inequities. In conjunction with class lectures, students viewed the exhibit and submitted a survey and a reflective essay about human rights abuses, as well as possibilities for realizing the right to health in the United States. Contrary to our expectations, the human rights issues surrounding the AIDS epidemic raised very little interest among our students, for whom AIDS is a preventable and treatable chronic disease. Instead, students were most interested in exhibits on eugenics and forced sterilization, deficits in water and sanitation, racism, and contradictions of American exceptionalism. We conclude that an emphasis on the violations of human rights and their health effects using domestic examples from relatively recent history can be an effective pedagogical strategy. This approach represents an opportunity to counter students’ presumptions that the United States exists outside of the human rights discourse. Moreover, this approach may reinforce the idea that the domestic race- and class-based inequalities can and should be understood as human rights violations.